\FOREIGN CORRESPONCE: ELT AUTHORS IN FRANCE AND OTHER EUROPEAN COUNTRIES. - Coustillas, Pierre (English Literature in Transition, 1880-1920, 1985)
Provides an overview of the literary works of ELT authors published and translated by an increasing number of publishers in France and other European countries. Period covered by the literary works; Collections of short stories reissued by the Presses Universitaires de Lille; Catalogues of the main paperback series published by major commercial publishers.